A DFT study of the adsorption energy and electronic interactions of the SO2 molecule on a CoP hydrotreating catalyst. Issue 5 (13th January 2021) - Bahamon, Daniel; Khalil, Malathe; Belabbes, Abderrezak; Alwahedi, Yasser; Vega, Lourdes F.; Polychronopoulou, Kyriaki
Abstract : The adsorption energy and electronic properties of sulfur dioxide (SO2 ) adsorbed on different low-Miller index cobalt phosphide (CoP) surfaces were examined using density functional theory (DFT). Abstract : The adsorption energy and electronic properties of sulfur dioxide (SO2 ) adsorbed on different low-Miller index cobalt phosphide (CoP) surfaces were examined using density functional theory (DFT). Different surface atomic terminations and initial molecular orientations were systematically investigated in detail to determine the most active and stable surface for use as a hydrotreating catalyst. It was found that the surface catalytic reactivity of CoP and its performance were highly sensitive to the crystal plane, where the surface orientation/termination had a remarkable impact on the interfacial chemical bonding and electronic states toward the adsorption of the SO2 molecule. Specifically, analysis of the surface energy adsorption revealed that SO2 on Co-terminated surfaces, especially in (010), (101) and (110) facets, is energetically more favorable compared to other low index surfaces. Charge density difference, density of states (DOS) and Gibbs free energy studies were also carried out to further understand the bonding mechanism and the electronic interactions with the adsorbate. It is anticipated that the current findings will support experimental research towards the design of catalysts for SO2 hydrodesulfurization based on cobalt phosphide nanoparticles.